Implementing Flipped Classroom to Enhance Students’ Engagement in College level under National University Bangladesh - Shakil, Md. Shakilur Zaman (Basic and Applied Education Research Journal, 2023)
Because of traditional classroom approach, lacking of engagement in classroom of honors level students under National University, Bangladesh is a very common scenario. So that, a large percentage of college graduates are found to be unemployed. The aim of this study is to find out possible solution of this instructional issue. Flipped classroom approach is a fruitful teaching strategy to deal with the problem. Flipped classroom method enhances students’ engagement in class. Students found pleasure and satisfaction to learn a new thing in a flipped classroom. Their class performance and attendance rate increased.